Mechanical engineering emerging vistas - Gupta, B. D. (Narosa Publishing House, 2011)
MECHANICAL ENGINEERING: Emerging Vistas discusses the recent developments in the ever-expanding areas of Mechanical Engineering viz. Material and Composites, Advanced Manufacturing Process, Computer Aided Design and Analysis, Ergonomics, Alternative Energy Sources and Thermal Engineering are opening up new vistas of venture and exploration. The studies included in this volume brew with Micro-Electro Mechanical Systems, Aerospace Engineering, Bio-Engineering and Energy which are multidisciplinary fields that hold enormous opportunities for Mechanical Engineers. Finite Element Methods, Human Body Vibration, Soft Computing Techniques like Fuzzy Decision Theory; Artificial Neural Network etc. make this volume a good exposition of knowledge. It is hoped that this will help young research and academics to adopt a holistic and sustainable approach to the development of modern world of which we are an integral part.